Liquidity and sovereignty: The Eurozone needs a lender of last ressort - Heribert Dieter (Stiftung Wissenschaft und Politik (SWP), 2010)
The financial crisis that hit Greece in early 2010 has demonstrated a fundamental weakness in the construction of the eurozone. The assumption that the criteria of Maastricht for fiscal policy would be sufficient to exclude liquidity crises has been proven false. The eurozone needs a lender of last resort that supports member countries in the event of liquidity shortages. However, theses credit lines should only be given if sufficient collateral can be provided. Nonetheless, the provision of a last-resort lending mechanism within the eurozone does not rule out the possible bankruptcy of a member state
Keywords: 320